Staging practices and breast cancer stage among population-based registries in the MENA region. (December 2022) - Piñeros, Marion; Ginsburg, Ophira; Bendahhou, Karima; Eser, Sultan; Shelpai, Wael A.; Fouad, Heba; Znaor, Ariana; ,; Hammouda, Doudja; Bouzbid, Sabiha; Beichi, Fayçal; Bouharati, Khaoula; et al.
Abstract: Background: Availability of stage information by population-based cancer registries (PBCR) remains scarce for diverse reasons. Nevertheless, stage is critical cancer control information particularly for cancers amenable to early detection. In the framework of the Global Initiative for Cancer Registry Development (GICR), we present the status of stage data collection and dissemination among registries in the Middle East and Northern Africa (MENA) region as well as the stage distribution of breast cancer patients. Methods: A web-based survey exploring staging practices and breast cancer stage was developed and sent to 30 PBCR in 18 countries of the MENA region. Results: Among 23 respondent PBCR, 21 collected stage data, the majority (80%) for all cancers. Fourteen registries used a single classification (9 TNM and 5 SEER), 7 used both staging systems in parallel. Out of 12, 888 breast cancer patients (seven registries) 27.7% had unknown TNM stage (11.1% in Oman, 46% in Annaba). When considering only cases with known stage, 65.3% were early cancers (TNM I+II), ranging from 57.9% in Oman to 83.3% in Batna (Algeria), and 9.9% were stage IV cancers. Among the nine registries providing SEER Summary stage for breast cancer cases, stage was unknown in 19% of the cases, (0 in Bahrain, 39% in Kuwait). Stage data were largely absent from the published registry reports. Conclusion: Despite wide stage data collection by cancer registries, missing information and low dissemination clearly limit informing efforts on early detection. The use of two classification systems in parallel implies additional workload and might undermine completeness. The favourable results of early cancer (TNM I+II) in two thirds of breast cancer patients needs to be interpreted with caution and followed up in time. Although efforts to improve quality of stage data are needed, our findings are particularly relevant to the WHO Global Breast Cancer Initiative. Highlights: Stage data are widely collected by population-based cancer registries (PBCR) in 16 MENA countries. Stage data were scarcely included in the registry reports. Both TNM and SEER classifications are used by PBCR in this region. Amongst 13, 000 breast cancer patients across 23 PBCR, slightly more than 65% were diagnosed at early stages (TNM I, II). The quality and dissemination of stage information needs improvement to better inform cancer control.